Geochemical Composition of Surface Sediments in the Bashang Area, North China and its Environmental Significance - Liu, Linjing; Jiang, Gaolei; Mao, Xin; Zhao, Hongmei; Zhao, Yongjie; Li, Yuecong; Zhao, Hua; Bi, Zhiwei (Frontiers in Earth Science, 2022)
The geochemical characteristics of sediments are important for reconstructing paleoclimatic and paleoenvironmental conditions in the Asian summer monsoon marginal area. However, robust reconstructions require an understanding of the key factors and mechanisms governing the spatial variations in the composition and ratio of chemical elements in the modern sediments of the Asian summer monsoon marginal area. In this study, 128 surface sediment samples were collected from the Bashang area, which is situated in the Asian summer monsoon marginal area, and examined for their major and trace element compositions and grain size. Principal component analysis (PCA) and redundancy analysis (RDA) were used to analyse the relationship between geochemical data and modern temperature and precipitation data. The results showed that the CIA values of sediments in the Bashang area are mainly affected by temperature rather than precipitation and the Rb/Sr value in the study area reflects the level of precipitation in the corresponding period and the temperature controlling the leaching and weathering. In addition, SiO2/Al2O3 and Zr/Ti ratios have good positive relationships with the coarse-grained fraction of sediments and thus can be used as grain size proxies. We propose that the exact environmental significance indicated by these proxies should be stated explicitly before using them as proxies for paleoenvironmental reconstructions of the Asian summer monsoon marginal area.